An analysis of three common sweat equity arrangements in family farm succession planning - Krultz, Jenn D. (Kansas State University, 2022)
Approximately 84% of assets on U.S. farms are represented in land ownership. Land values have dramatically increased over the past 50 years, while commodity price trends have paled in comparison. As farmers look to retire and successfully transition their farms to the next generation, it may be necessary to rely on sweat equity to compensate a returning heir as sufficient cash may not be available in any given year. Sweat equity can be defined as a scenario in which an on-farm heir is paid below-market rates for work in the business. Instead of cash, compensation can be in the form of assets or commodities. While there is plenty of research and resources available on-farm estate and succession planning, there is not a lot of emphasis on sweat equity arrangements. How can a retiring farmer and heir set up an agreement to ensure that the heir’s unpaid efforts will be compensated fairly when the family farm transitions? Three simulation farms are created using Kansas Farm Management Association data regarding farm income, expenses, debt, and family living expenses. Three sweat equity arrangements are applied to each farm to determine which arrangements provide the highest cash and sweat equity values to ensure the success of each farm for both the retiring generation and the returning heir. Results found all three scenarios to be successful for each farm, with the arrangement that the heir receiving a percentage of the total net income to be the most successful. The arrangement of the retiring generation providing an annual salary to the returning heir also provided profitable results. While providing the least amount of cash savings, an arrangement to pay the returning heir hourly was also a feasible option.
Keywords: Succession planning; Sweat equity; Farm transition; Percentage agreement; Salary agreement; Hourly agreement